2020
DOI: 10.1186/s12944-020-01409-1
|View full text |Cite
|
Sign up to set email alerts
|

Association between triglyceride glucose-body mass index and non-alcoholic fatty liver disease in the non-obese Chinese population with normal blood lipid levels: a secondary analysis based on a prospective cohort study

Abstract: Background Both triglyceride glucose-body mass index (TyG-BMI) and non-alcoholic fatty liver disease (NAFLD) are linked to insulin resistance (IR). Prospective studies linking TyG-BMI to NAFLD have been limited by short follow-up. This study investigated the longitudinal association between TyG-BMI and NAFLD occurrence in the non-obese Chinese individuals. Methods This study determined TyG-BMI at baseline and the incidence of NAFLD a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
47
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(50 citation statements)
references
References 44 publications
3
47
0
Order By: Relevance
“…As expected, several anthropometric or metabolic indices such as skeletal muscle mass [16], atherogenic index [17,18], Body Mass Index (BMI) [19], the ratio of Triglyceride (TG) to High-Density Lipoprotein cholesterol [20], visceral adipose tissue [21], Total cholesterol (TC) to High-Density Lipoprotein cholesterol ratio [22] and Triglyceride Glucose (TyG) [23,24], as well as blood pressure [25] had been reported to be associated with FL in both cross-sectional and cohort studies. However, most existing studies mainly focused on only one or two indices, which might have limitations for predicting FL considering the high complexity of the pathogenesis of FL.…”
Section: Introductionsupporting
confidence: 63%
See 1 more Smart Citation
“…As expected, several anthropometric or metabolic indices such as skeletal muscle mass [16], atherogenic index [17,18], Body Mass Index (BMI) [19], the ratio of Triglyceride (TG) to High-Density Lipoprotein cholesterol [20], visceral adipose tissue [21], Total cholesterol (TC) to High-Density Lipoprotein cholesterol ratio [22] and Triglyceride Glucose (TyG) [23,24], as well as blood pressure [25] had been reported to be associated with FL in both cross-sectional and cohort studies. However, most existing studies mainly focused on only one or two indices, which might have limitations for predicting FL considering the high complexity of the pathogenesis of FL.…”
Section: Introductionsupporting
confidence: 63%
“…The fatty liver-related indices, including WHtR, WHR, BMI, AVI, AIP, TyG and ALT/AST were calculated using the following equations [18,19,23,27]. BMI = weight (kg) / height 2 (m) WHtR = WC (cm) / height (cm) WHR = WC (cm) / HC (cm) AVI = [2 × WC 2 (cm) + 0.7×(WC − HC) 2 (cm)]/1000 AIP = Ln [TG (mmol/L)) / HDL (mmol/L)] TyG = Ln [TG (mg/dL) × FBG (mg/dL)/2] ALT/AST = ALT(U/L) / AST (U/L) Diagnoses of FL was based on the four abdominal ultrasonography standard (parenchymal brightness, hepatorenal echo contrast, deep beam attenuation, and bright vessel walls) by experienced radiologists with expertise in liver imaging [28,29].…”
Section: Data Collectionmentioning
confidence: 99%
“…The conclusions of several existing studies are controversial, and do not include TyG indexrelated parameters [21][22][23]. According to some recent studies, TyG index-related parameters are promising new indicators for predicting NAFLD [14,24]. It is critical to further compare TyG index-related parameters with other obesity and lipid-related indices and identify more useful biomarkers for predicting NAFL D. Therefore, the present study was designed to evaluate the best obesity and lipid-related indices for predicting NAFLD through an epidemiological survey of 14251 from the general population who underwent health screening.…”
Section: Introductionmentioning
confidence: 99%
“…Another study showed that the association of TyG and NAFLD risk was signi cantly stronger in nonobese subjects than that in obese ones [18]. Thus, the predictive power of TyG index for NAFLD risk was partially affected by BMI of the individuals.…”
Section: Discussionmentioning
confidence: 97%
“…Although most studies explored the relationship between the TyG index and NAFLD risk, these studies focused on the general population [15,18,19]. Our present study focused on the associations of the TyG index, glycemic parameters, and lipid parameters with NAFLD in a T2DM population.…”
Section: Discussionmentioning
confidence: 99%